Corporate Crisis Communication Strategy of HENKEL Indonesia in Facing the Covid-19 Pandemic - Atika Budhi Utami; Widya Hamdani; Faris Budiman Annas (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
The covid-19 pandemic has affected the world, including Indonesia, specifically the certainty of the company's economic sustainability. This requires each organization to execute strategic communication with its employees. Henkel Indonesia carried out a communication strategy during a crisis to provide certainty and eliminate uncertainty to its employees. This study aimed to discover how it implemented strategic communication crises. It also strengthens the concept of a Situational Crisis Communication Theory, which elaborates into a tactical, planned, measurable, and able-to-evaluate crisis communication strategy. This research explored the crisis response strategies that the company applied in dealing with the pandemic. The methodology used in this research is qualitative. Qualitative research consists of a set of interpretive and material practices that make the world visible. The method used in this research is a case study. The unit of analysis in this study is a group of the Human Resources Department. The results of this study revealed that the company activated the Crisis Management Team by executing extensive security, hygiene, and social distancing measures to protect employees from spreading the virus in the work area. It used diminishing strategies in the Situational Crisis Communication Theory and implemented excuse and justification communication techniques. The crisis communication strategy conducted by the company has a positive impact on its employees. The limitation of this study is that it focused solely on the crisis communication strategy from the company-employee perspective. This research did not reach external stakeholders. Keywords:   Crisis Communication; Employee; Pandemic; Situational Crisis